Corrigendum to Interleaved step-up soft-switching DCDC Boost converter without auxiliary switches [Energy Rep. 8 (2022) 64996511, (Energy Reports (2022) 8(6499-6511) (S2352484722008320), (10.1016/j.egyr.2022.04.069)) - Rezvanyvardom M.; Mirzaei A.; Shabani M.; Mekhilef S.; Rawa M.; Wahyudie A.; Ahmed M. (Elsevier Ltd, 2023)
The authors regret <The affiliation of Muhyaddin Rawa is Smart Grids Research Group, Center of Research Excellence in Renewable Energy and Power Systems, King Abdulaziz University, Jeddah 21589, Saudi Arabia >. The authors would like to apologise apologize for any inconvenience caused. 2022